Hygiene Practices and Airborne Microbial Concentrations in Restaurants - Haruna Gulumbe, Bashar; Hassan Kawo, Abdullahi; Bashar Danlami, Mohammed; Bello, Muhammad (International Journal of Environment, 2019)
This study was carried out to evaluate bioaerosol concentrations in the indoor air and the hygiene practices of restaurants to highlight the exposure risks and improve food safety in restaurants. Using depositional sampling techniques, air samples were collected from each restaurant kitchen and dining room and aerobically cultured. Hygiene/sanitary conditions were assessed using observation schedules and questionnaires. Meteorological parameters were also monitored during air sampling. The results revealed that bacterial and fungal concentrations (CFU m-3) ranged from 1.07×103‒1.36×104 and 8.2×101‒5.76×102, respectively. Regarding the sanitary conditions of the restaurants, 3.5% of the kitchens were in good sanitary condition, and the food was adequately protected from flies in only 14% of the kitchens. Only 3.5% of the food handlers had attended food hygiene basic training, up to 33% of the food handlers had no education at all, and only 0.10% had medical certifications. High microbial counts and the poor sanitary conditions and personal hygiene practices observed in this study not only indicate a strong need for improved hygiene but also constitute a serious potential health hazards.